2020
DOI: 10.1021/acssensors.9b02490
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive Detection of Broad-Spectrum Bacteria with Small-Molecule Fluorescent Excimer Chemosensors

Abstract: Antibiotic resistance is a major problem for world health, triggered by the unnecessary usage of broad-spectrum antibiotics on purportedly infected patients. Current clinical standards require lengthy protocols for the detection of bacterial species in sterile physiological fluids. In this work, a class of small-molecule fluorescent chemosensors termed ProxyPhos was shown to be capable of rapid, sensitive, and facile detection of broad-spectrum bacteria. The sensors act via a turnon fluorescent excimer mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…The dpa group, which is a phosphate sensor, forms a complex with phosphate and metal ions such as Cu 2+ [ 22 ] or Zn 2+ [ 23 ]. One research group has recently reported that some bacterial components were detected by dpa sensors using flow cytometry analysis [ 24 ]. The electrostatic interaction between the cationic amine group and the negatively charged bacterial surface has also been studied [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…The dpa group, which is a phosphate sensor, forms a complex with phosphate and metal ions such as Cu 2+ [ 22 ] or Zn 2+ [ 23 ]. One research group has recently reported that some bacterial components were detected by dpa sensors using flow cytometry analysis [ 24 ]. The electrostatic interaction between the cationic amine group and the negatively charged bacterial surface has also been studied [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Excimer is defined as a dimer associated with an excited electronic state and dissociative in its ground electronic state. Generally, the excimer band shows a red shift compared with a monomer because of the increasing electron affinity of the acceptor and decreasing the donor’s ionization potential. Using the fluorescence properties of excimers, the fluorescent sensor molecules for heavy and transition metals have been extensively developed. Among well-known fluorophores, anthracene, pyrene, and their derivatives have been investigated into many functions for sensing metal ions, pH, simple inorganic anions, and small organic molecules. Pyrene is strong electron donor material, and pyrene excimer from several pyrene derivatives usually exhibits a similar emission color of sky-blue or cyan, resulting from almost the same excited-state geometry. Since excellent monomer and excimer emission changes occur at remarkably different wavelengths on the basis of the distance between two anthracene or pyrene moieties, both fluorophores (anthracene and pyrene) acting as a fluorophore have been utilized effectively. …”
Section: Introductionmentioning
confidence: 99%
“…10,11 Fluorescent methods employ various organic dyes to differentiate living and dead bacterial cells. [12][13][14][15] Although rapid and easy to operate, these uorescent methods rely on costly uorescent dyes and require complex instruments such as laser scanning confocal microscopy 16 or ow cytometry, 17 which impede their widespread applications in resource-limited regions. Therefore, there is an urgent need to develop a rapid, simple, and low-cost method for measuring bacterial viability.…”
Section: Introductionmentioning
confidence: 99%